2015
DOI: 10.1002/adhm.201570064
|View full text |Cite
|
Sign up to set email alerts
|

Nanocapsules: Macrophage Cell Membrane Camouflaged Mesoporous Silica Nanocapsules for In Vivo Cancer Therapy (Adv. Healthcare Mater. 11/2015)

Abstract: On page 1645 Q. He, J. Li and colleagues present natural macrophage cell membrane camouflaged silica nanocapsules through a top‐down assembly. The employed cell membrane coating can effectively weaken immune response in biological entity, and achieve longer survival time and higher accumulation in the tumor. This strategy supplies a high‐efficiency delivery platform for in vivo transportation such as drugs and imaging probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…[ 172 ] This property enables macrophage membranes have attracted researchers' attention as a kind of bacterial targeting material. [ 173 ] For example, Wang et al [ 164 ] reported a gold and silver nanocage (GSNC) coated with macrophage membrane by extrusion technique. Due to the bacterial recognizing receptors on macrophage membranes, macrophage membranes‐coated GSNC could be effectively enriched in the infection site.…”
Section: Super‐antibacterial Systemsmentioning
confidence: 99%
“…[ 172 ] This property enables macrophage membranes have attracted researchers' attention as a kind of bacterial targeting material. [ 173 ] For example, Wang et al [ 164 ] reported a gold and silver nanocage (GSNC) coated with macrophage membrane by extrusion technique. Due to the bacterial recognizing receptors on macrophage membranes, macrophage membranes‐coated GSNC could be effectively enriched in the infection site.…”
Section: Super‐antibacterial Systemsmentioning
confidence: 99%
“…[85] In the field of nanomedicine, imaging and phototherapy play an important role in expanding the functions of nanomaterials. [224] Considering their therapeutic application in drug delivery, potential cancer treatment was investigated by modifying and encapsulating nanomaterials within different types of membrane vesicles, including RBC, macrophage, platelet, and other membrane vesicles, [103,225,226] as encapsulation within membrane vesicles could reduce immune clearance. [227] Piao et al used an RBC membrane vesicle encapsulating a gold nanocage against a murine 4T1 tumor model and elevating the temperature from 35 to 41 °C using NIR irradiation for 10 min.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Besides the RBC membrane, the He group recently explored different cell membranes‐functionalized particles for the applications of biomimetic drug delivery. For example, the macrophage cell membrane‐derived nanovesicles were prepared and modified onto the mesoporous silica nanocapsules . The resulting biointerfacing nanocapsules showed the evading capability of the immune attack for prolonged period in vivo, and target location in tumor sites.…”
Section: Biointerfacing Of Controlled Assembled Micro/nanomotorsmentioning
confidence: 99%